2008
DOI: 10.1002/anie.200800034
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Potassium‐Functionalized Mesoporous γ‐Alumina: A Solid Superbase

Abstract: Basically super: Potassium‐functionalized mesoporous γ‐alumina solid superbases that have a high base strength (H−) of 27.0, a well‐expressed mesoporous structure, and which are efficient in the isomerization of 1‐hexene are synthesized by a one‐pot method. The success of this method can be ascribed to the flexible application of K2CO3 as a pH adjustor and close control of the calcination process (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 24 publications
10
65
0
Order By: Relevance
“…Figure 3 shows the IR spectra of KNO 3 -Y treated at different conditions. The bands at 1,385 and 830 cm -1 observed on the as-prepared KNO 3 -Y sample can be assigned to nitrate anion (curve a1) [20]. These IR bands nearly kept constant after the sample was activated at 600°C (curve a2).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Figure 3 shows the IR spectra of KNO 3 -Y treated at different conditions. The bands at 1,385 and 830 cm -1 observed on the as-prepared KNO 3 -Y sample can be assigned to nitrate anion (curve a1) [20]. These IR bands nearly kept constant after the sample was activated at 600°C (curve a2).…”
Section: Resultsmentioning
confidence: 93%
“…The spectra were collected with 2 cm -1 resolution. The strength of the basic sites was measured by titration in cyclohexane using a series of Hammett indicators [20]. The samples were activated at 600°C in a flow of N 2 (30 mL min -1 ) for 2 h before measurement.…”
Section: Characterizationmentioning
confidence: 99%
“…However, besides the crystal phase, other factors, including the specific surface area, crystal composition, material microstructures, and the absence of exotic species from the remnant starting materials, also significantly affect the catalytic performance. [113][114][115][116] In this case, the special hierarchical structures of the amorphous hncp alumina array have porous structures and possess a much higher specific surface area than the dense alumina film, which, together with the pure compositions, contributes to better catalytic properties.…”
Section: Enhanced Catalytic Propertiesmentioning
confidence: 99%
“…In the development of environment-benign processes, they are used as catalysts so that reactions can be conducted under mild conditions and without generation of much waste [1][2][3]. In the past two decades, there were many reports on solid superbases such as NaN 3 /c-Al 2 O 3 [4], Na/NaOH/c-Al 2 O 3 [5], K/MgO [6], Eu 2 O 3 /c-Al 2 O 3 [7], KNO 3 /c-Al 2 O 3 [8], KNO 3 /ZrO 2 [9], KOH/ZrO 2 [10], KF/c-Al 2 O 3 [11], and Ca(NO 3 ) 2 /SBA-15 [12]. Recently, we found that the solid superbases Na 2 SnO 3 [13,14] and KOH/La 2 O 3 -MgO [15] showed excellent catalytic efficiency towards some organic reactions at room temperature (RT).…”
Section: Introductionmentioning
confidence: 99%